Pemanfaat Aplikasi Mendeley dalam Penulisan Tugas Akhir oleh Mahasiswa Program Studi Ilmu Perpustakaan Universitas Islam Negeri Sumatera Utara - Nurul Adilla; Nurhayani Nurhayani (Reslaj: Religion Education Social Laa Roiba Journal, 2023)
Lots of library processing applications can be used to support students in completing their final assignments, one of which is through Mendeley. Mendeley is an application that has the ability to process scientific databases in the form of e-books, e-journals, and other libraries. Mendeley is claimed to be important in writing the final project because reference management can make it easier for the civitas academica to cite citations as well as good reference management and can minimize plagiarism. This study discusses the Utilization of the Mendeley Application in Writing Final Projects by Library Science Study Program Students at the State Islamic University of North Sumatra in writing scientific articles for Library Science study program students. This study aims to find out how to use Mendeley in writing their final assignment by Library Science students at the State Islamic University of North Sumatra. This research method uses qualitative methods with observation and interview approaches. The research subjects were students of the 2019 Library Science study program who were writing their final assignment.